Withdrawal from chronic treatment with methamphetamine induces anxiety and depression-like behavior in mice. (January 2019) - Ru, Qin; Xiong, Qi; Zhou, Mei; Chen, Lin; Tian, Xiang; Xiao, Huqiao; Li, Chaoying; Li, Yi
Highlights: Withdrawal from chronic METH treatment increased anxiety and depression-like behavior. Levels of key molecules of BDNF pathway in hippocampus and prefrontal cortex were changed. Expressions of BDNF, p-TrkB, p-ERK1/2 and p-CREB were decreased in METH group. BDNF pathway may be involved in psychiatric symptoms induced by withdrawal from METH. Abstract: Methamphetamine (METH) is an illicit psychostimulant that is widely abused. After producing extreme pleasure, METH abuse leads to negative emotional states during withdrawal in clinical survey. However, the mood behavioral consequences of withdrawal from chronic METH exposure in animal experiments and related mechanisms have not been clarified yet. The aim of this study was to investigate the anxiety and depression-like phenotype in mice induced by withdrawal from chronic METH treatment and the potential molecular mechanism. We found that withdrawal from chronic METH treatment increased the immobility time during the forced swimming test and decreased central activities in open field test, indicating increased anxiety and depression-like behavior. Additional experiments showed that expression of brain-derived neurotrophic factor (BDNF), phosphorylated tropomyosin receptor kinase B (p-TrkB), phosphorylated extracellular signal-related kinase 1/2 (p-ERK1/2) and phosphorylated cAMP-response element binding protein (p-CREB) were decreased in the hippocampus and prefrontal cortex of mice in METH group and the level of mitogen activated protein kinase phosphatase-1 (MKP-1) was increased. Combined, our data show that withdrawal from chronic METH exposure induces anxiety and depression-like behavior associated with aberrant changes of proteins in BDNF-ERK-CREB pathway, providing new evidence for the involvement of BDNF pathway in the negative emotional states induced by withdrawal from METH.